A semantic datagrid for combinatorial chemistry. - Taylor, K; Gledhill, R; Essex, J; Frey, J; Harris, S; Roure, D (IEEE, 2005)
The CombeChem project has designed and deployed an e-Science infrastructure using a combination of Grid and Semantic Web technologies. In this paper we describe the datagrid element of the project, which provides a platform for sophisticated scientific queries and a rich record of experimental data and its provenance. This datagrid constitutes a significant deployment of Semantic Web technologies and we propose it as an example of a 'Semantic Datagrid'. © 2005 IEEE.